Application of The Problem Based Learning Model to Improve Mathematical Representation Capability Class X.2 Students of SMAN 6 Pekanbaru - Saragih, Soni Ezra Ridwana; Siregar, Syarifah Nur; Murni, Atma (Journal of Educational Sciences, 2025)
This research aims to improve the learning process and increase students' Mathematical Representation Ability (MRA) through the application of the Problem Based Learning (PBL) model. The form of this research is Classroom Action Research (CAR) with 2 cycles carried out in class The research instrument consists of learning tools (learning objective flow and teaching modules) and data collection instruments (observation sheets and MRA tests). Based on the results of the analysis of teacher and student activities as a whole, it was found that there was an improvement in the quality of the implementation of the learning process. The results of the MRA test analysis show that the average MRA score of students in the initial test was 40.85 in the low category and increased in cycle 1 to an average of 54.81 in the medium category and in cycle 2 the average gain in MRA scores amounting to 75.69 in the high category. Based on the results of the analysis, it was found that the PBL model can improve the quality of implementation of the learning process and increase students' MRA.